Global Supply Chain Strategy in the Cooperation of Russia and Tajikistan in the Field of Security in the Early 21st Century - Beloglazov, A.V.; Mubarakshina, A.M.; Zakirov, A. (International Journal of Supply Chain Management, 2019)
The article is devoted to the cooperation of the Russian Federation and the Republic of Tajikistan in the sphere of security in the period from 2000 to 2017. It explores the relations of the two states in the political and military-technical spheres in the context of Eurasian integration processes. Some economic, cultural and humanitarian aspects of cooperation are also considered, complementing the security policy with elements of "soft power". Particular attention is paid to bilateral meetings and political decisions of the presidents of Russia and Tajikistan. In addition, the influence of the Afghan factor on the situation in Tajikistan is revealed and Russia's policy on its neutralization is disclosed to ensure regional security.